Research and development of integrative treatment system of municipal solid waste and its key techniques - SHENG Kui-chuan; LIN Fu-cheng; MIN Hang (浙江大学学报. 农业与生命科学版, 2005)
The actualities of disposal or treatment of municipal solid waste (MSW) in Zhejiang Province were reviewed, and the imperfection and limitation of MSW disposal by a single way, such as landfill, incineration and composting, were summarized and discussed in the paper. As an advanced way, the integrative treatment is apt to actualize the principles of reutilization, minimization and innocuity of MSW. The system of integrative treatment based on recycling, composting, incineration and landfill of MSW was put forward. Finally, the key techniques of the realization of the integrative treatment were discussed.